Self-Esteem and Spiritual Intelligence as Predictors of Students’ Understanding of Sexual Violence - Astrid; Nur Afiah (Journal of Islamic Communication and Counseling, 2026)
Sexual violence in higher education continues to increase and poses serious consequences for students, making an adequate understanding of this issue critically important. This study aims to analyze the influence of self-esteem and spiritual intelligence on students’ understanding of sexual violence. A quantitative approach was employed using multiple linear regression analysis involving 213 active university students. The research instruments included self-esteem, spiritual intelligence, and sexual violence understanding scales. The results indicate that spiritual intelligence has a significant effect on students’ understanding, whereas self-esteem does not show a significant influence. The regression model explains 77.1% of the variance in students’ understanding, suggesting that spiritual intelligence plays a crucial role in shaping moral awareness and students’ ability to recognize and evaluate acts of sexual violence. These findings highlight the importance of integrating moral and spiritual values into higher education as a preventive effort against sexual violence and in fostering a safe and responsive academic environment.